2020
DOI: 10.1101/2020.05.17.20101451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Antibodies Targeting a Transporter Mediate Protection Against Tuberculosis

Abstract: Evidence has emerged that some healthy individuals with a history of exposure to Mycobacterium tuberculosis (Mtb) can develop protective antibody responses. However, it is not known whether patients with active tuberculosis elicit protective antibodies, and if they do, which bacterial antigens are targeted. To investigate the B cell responses during active infection, we generated a panel of monoclonal antibodies isolated from memory B cells of one patient. The antibodies, members of four distinct B cell clones… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Some scholars believed that most of the studies on PTB patients examined B cells isolated from peripheral blood and not in amed Mtbaffected tissues, which led to inconsistent conclusions on B cell levels in PTB 8 . There were experimental results to prove that inhibitory anti-PstS1 B cell responses arise during active tuberculosis 9 . The result of this study showed that the expression of B cells was higher in PTB.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars believed that most of the studies on PTB patients examined B cells isolated from peripheral blood and not in amed Mtbaffected tissues, which led to inconsistent conclusions on B cell levels in PTB 8 . There were experimental results to prove that inhibitory anti-PstS1 B cell responses arise during active tuberculosis 9 . The result of this study showed that the expression of B cells was higher in PTB.…”
Section: Discussionmentioning
confidence: 99%